183k views
4 votes
Write the quadratic function in vertex form.

y = x2 - 2x + 5

y = (x + 1)2 - 4
y = (x - 1)2 - 4
y = (x + 1)2 + 4
y = (x - 1)2 + 4

2 Answers

2 votes
I think the answer would look something like this Y-4=(x-1)^2
User Bragboy
by
5.7k points
6 votes

Answer:

The answer to your question is y = (x - 1)² + 4

Explanation:

y = x² - 2x + 5

Complete perfect square trinomial

y - 5 = x² - 2x

y - 5 + ( )² = x² - 2x + ( )²

y - 5 + (1)² = x² - 2x + (1)²

y - 5 + 1 = x² - 2x + 1

Factor and simplify y - 4 = (x - 1)²

y = (x - 2)² + 4

User Kishore A
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.